FILSAFAT PROGRESIVISME DAN IMPLIKASINYA BAGI PENDIDIKAN ISLAM - Sigit Tri Utomo; Luluk Ifadah (Wahana Islamika: Jurnal Studi Keislaman, 2020)
This research is a qualitative study using a library approach, the object of the material is the relevance of the philosophy of progressivism and its implications for Islamic education. The data collection method in this research uses literature study. In this stage, the researcher tries to select data (books) that are relevant to the philosophy of progressivism and its implications for Islamic education. In this paper the analysis used with hermeneutics, this method step is intended to capture the meaning, value and purpose of the relevance of philosophy of progressivism and its implications for Islamic education. Then the authors also use synthesis analysis means the stages of an object of scientific study that connects an articulation of meaning with one another meaning which is then discovered by a new articulation of knowledge in the form of the philosophy of progressivism and its implications for Islamic education. The author also uses content analysis about the content of the philosophy of progressivism and its implications for Islamic education. The results showed that the flow of philosophy of progressivism was the flow of modern educational philosophy which required a change in the implementation of education to be more advanced. This flow of progressivism prioritizes the implementation of education in children-centered schools (student-oriented) and makes educators limited to being facilitators, mentors, and directors for students. The purpose of the flow of progressivism in education is to want to change the practice of education that has been impressed authoritarian to be democratic and more respectful of the potential and abilities of children and encourage the implementation of learning that involves more students. By implementing the flow of progressivism in education, the hope is that it can bring change and progress in education in Indonesia to become more quality, so that it can realize the goals of Indonesia's national education